Exploring Mispricing in the Term Structure of CDS Spreads. (8th May 2018) - Jarrow, Robert; Li, Haitao; Ye, Xiaoxia; Hu, May
Abstract: Based on a reduced-form model of credit risk, we explore mispricing in the credit default swaps (CDS) spreads of North American companies and its economic content. Specifically, we develop a trading strategy using the model to trade out of sample market-neutral portfolios across the term structure of CDS contracts. Our empirical results show that the trading strategy exhibits abnormally large returns, confirming the existence and persistence of a mispricing. The aggregate returns of the trading strategy are positively related to the square of market-wide credit and liquidity risks, indicating that the mispricing is more pronounced when the market is more volatile. When implemented on the Markit data, the strategy shows significant economic value even after controlling for realistic transaction costs.